The Influence of Digital Technology and Work Facilities on Performance Through Employee Job Creativity at the Inspectorate of East Java Province - Dias Sukmahati, Rany; B. Setiadi, Pompong; Dwi, Fanny (Jurnal Ekonomi, 2024)
This thesis investigates the impact of digital technology and work facilities on employee performance through the mediating role of job creativity at the Inspectorate of East Java Province. The study aims to examine the direct influence of digital technology and work facilities on job creativity and, subsequently, their combined effect on employee performance. Utilizing a quantitative research approach, data will be collected from employees within the Inspectorate of East Java Province. The findings are expected to provide insights into the intricate relationships between digital technology, work facilities, job creativity, and employee performance, contributing valuable knowledge for organizations seeking to enhance their workforce productivity in the digital era.